Popular Efficacy in the Democratic Era : A Reexamination of Electoral Accountability in the United States, 1828-2000 - Nardulli, Peter F. (Book collections on Project MUSE., 2005)
"In this book, Peter Nardulli challenges the conventional wisdom that citizens are "manageable fools," with little capacity to exercise independent judgment in the voting booth. Rather, he argues, voters are eminently capable of playing an efficacious role in democratic politics and of routinely demonstrating the ability to evaluate competing stewards in a discriminating manner."--Jacket